y"+y'-2y=0
Производим замену:
y"= ; y'=k ; y=1
+k-2=0
находим дискриминант: a=1, b=1,c=-2
D=-4ac=1-4*1*(-2)= 1+8=9
=3
Находим корни k1 и k2
Обратная замена:
y1 =
y2 =
Общее решение однородного уравнения имеет вид:
y=C1y1+C2y2
y"+y'-2y=0
Производим замену:
y"=
; y'=k ; y=1
находим дискриминант: a=1, b=1,c=-2
D=
-4ac=1-4*1*(-2)= 1+8=9
Находим корни k1 и k2
Обратная замена:
y1 =![e^{-2x} \\](/tpl/images/1179/8879/f39f9.png)
y2 =![e^{x}](/tpl/images/1179/8879/8110c.png)
Общее решение однородного уравнения имеет вид:
y=C1y1+C2y2